Data Management in Networks - Meyer auf der Heide, Friedhelm (Graph-Theoretic Concepts in Computer Science)

Parallel Bridging Models and Their Impact on Algorithm Design - Meyer auf der Heide, Friedhelm; Wanka, Rolf (Computational Science - ICCS 2001)

The Algorithms Behind GAIO — Set Oriented Numerical Methods for Dynamical Systems - Dellnitz, Michael; Froyland, Gary; Junge, Oliver (Ergodic Theory, Analysis, and Efficient Simulation of Dynamical Systems)

Extracting Dynamical Behavior via Markov Models - Froyland, Gary (Nonlinear Dynamics and Statistics)

Rigorous computation of topological entropy with respect to a finite partition - Froyland, Gary; Junge, Oliver; Ochs, Gunter (Physica D: Nonlinear Phenomena)

An adaptive subdivision technique for the approximation of attractors and invariant measures: proof of convergence - Junge, Oliver (Dynamical Systems)

Algorithms — ESA 2001, 9th Annual European Symposium Århus, Denmark

Glimpses into the Future of Computer Science Education - Domik, Gitta (J. (UCS))

The numerical detection of connecting orbits - Dellnitz, Michael; Junge, Oliver; Thiere, Bianca (Discrete & Continuous Dynamical Systems - B)

Object-oriented domain specific compilers for programming FPGAs - Mencer, Oskar; Platzner, Marco; Morf, Martin; J. Flynn, Michael (IEEE Transactions on Very Large Scale Integration (VLSI) Systems)

Implementation of a Rake Receiver Architecture into a Galileo Receiver - Bischoff, R.; Haeb-Umbach, Reinhold; Schulz, W.; Heinrichs, G. (1st ESA Workshop on Satellite Navigation User Equipment Technology (Navitec 2001))

Automatic generation of phonetic regression class trees for MLLR adaptation - Haeb-Umbach, Reinhold (IEEE Transactions on Speech and Audio Processing)
In this paper, it is shown that a correlation criterion is the appropriate criterion for bottom-up clustering to obtain broad phonetic class regression trees for maximum likelihood linear regression (MLLR)-based speaker adaptation. The correlation structure among speech units is estimated on the speaker-independent training data. In adaptation experiments the tree outperformed a regression tree obtained from clustering according to closeness in acoustic space and achieved results comparable with those of a manually designed broad phonetic class tree
Keywords: acoustic space; adaptation experiments; automatic generation; bottom-up clustering; broad phonetic class regression trees; correlation criterion; correlation methods; maximum likelihood estimation; maximum likelihood linear regression based speaker adaptation; MLLR adaptation; pattern clustering; phonetic regression class trees; speaker-independent training data; speech recognition; speech units; statistical analysis; trees (mathematics)

Multiclass linear dimension reduction by weighted pairwise Fisher criteria - Loog, M.; Duin, R.P.W.; Haeb-Umbach, Reinhold (IEEE Transactions on Pattern Analysis and Machine Intelligence)
We derive a class of computationally inexpensive linear dimension reduction criteria by introducing a weighted variant of the well-known K-class Fisher criterion associated with linear discriminant analysis (LDA). It can be seen that LDA weights contributions of individual class pairs according to the Euclidean distance of the respective class means. We generalize upon LDA by introducing a different weighting function
Keywords: approximate pairwise accuracy; Bayes error; Bayes methods; error statistics; Euclidean distance; Fisher criterion; linear dimension reduction; linear discriminant analysis; pattern classification; statistical analysis; statistical pattern classification; weighting function

Experience-based decision making and learning from examples - Hüllermeier, Eyke (In Proceedings SOR-01 Symposium on Operations Research, Duisburg, Germany)

Ultraschallgeschwindigkeitsmessung zum Bioprozessmonitoring - Cha, Y. L.; Hitzmann, Bernd; Bellgardt, Karl-Heinz; Daur, Peter-Christoph; Henning, Bernd
In diesem Beitrag werden Messungen und Auswertungen der Ultraschallgeschwindigkeitsmessung zur Überwachung von Hefekultivierungen vorgestellt. Die Ultraschallgeschwindigkeit ist abhängig von Biomasse-, Glukose- und Ethanolkonzentration, aber auch von anderen Bioprozessvariablen. Um den Einfluss von Blasen auf das Signal zu reduzieren, wurde der Ultraschallsensor in einem Bypass-System eingesetzt. Es wurden Messungen sowohl im Flow- als auch Stop-Flow-Betrieb durchgeführt. Um die richtigen Informationen aus diesem unspezifischen Signal zu erhalten, wurde ein multilineares Regressionsmodell berechnet, wobei die Biomasse-, Glukose- und Ethanolkonzentration als unabhängige Variablen dienten. Ein Beispiel der Ergebnisse ist in Abbildung eins gezeigt. Es sind die Biomasse-, Glukose- und Ethanolkonzentration während einer Saccharomyces cerevisiae Kultivierung dargestellt. Die Parameter des multilinearen Regressionsmodells wurden durch Verwendung der Daten aus der dargestellten Kultivierung identifiziert. Wird dieses Modell zur Auswertung auf die Signale anderer Prozesse übertragen, ist das Ergebnis ähnlich, jedoch vergrößert sich der Fehler der Schätzung. Die Ergebnisse sowie Erfahrungen werden ausführlich in dem Beitrag diskutiert.

Quality inspection and characterisation of ultrasonic sensor properties using a PC-controlled scanning measuring system - Henning, Bernd; Prange, Stefan; Dierks, Karsten; Daur, Peter-Christoph
Nowadays the use of ultrasonic sensors for process control for flow, level or concentration measurement is wide spread. In this application there are high demands for a defined and stable quality of the properties of such ultrasonic sensors. For the detailed investigation and characterization of ultrasonic sensor properties an efficient PC-controlled measuring system has been developed at ifak. In this report this new high performance approach will be presented to make the vibrating ultrasonic sensor surface and also the sound field in front of acoustic sensors in liquids visible.

Vom Modellieren zum Gestalten - Objektorientierung als Impuls für einen neuen Informatikunterricht? - Schulte, Carsten (Informatica Didactica)

Aufgabenbereiche der Medienbildung im Informatikunterricht - Schulte, Carsten; Scheel, Olaf (INFOS)

Possibilistic instance-based learning - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)

Implication-based fuzzy association rules - Hüllermeier, Eyke (In Proceedings FGML-2001 German Workshop on Machine Learning, Dortmund, Germany)